Enhancing estuarine flood risk management: comparative analysis of three estuarine systems - Rilo, Ana (2020)
Estuarine flood risk management is a challenge for coastal managers since this type of system is usually complex due to the presence of multiple trigger combinations that can induce flood events affecting different types of human occupation. Furthermore, legal directives demanded countries to have flood risk assessment tools therefore enhancing knowledge on estuarine triggers and flood damage typologies is useful for coastal managers. In this study three different flood events are compared and contrasted, each one having occurred in a different estuarine system chosen based on a set of criteria (temporal proximity, occurrence of human damages and at least three flood triggers identified in each database). The diversity of data sources that characterizes each database was examined, for the three events, which are described in terms of triggers and damages. The comparison highlighted that the local context was important in the estuarine flood combination of triggers and disclosed two categories (one category comprising infrastructure economic and human damages; and another category involving circulation interruption and functions disruption) of flood damages common between the studied systems corresponding to different levels of relevance for management. The enhanced knowledge acquired allowed the construction of a conceptual framework for damages that can contribute to more adequate estuarine flood risk frameworks.